An overview of heat sink technology - Ehsan F. Abbas (Zielona Góra: Uniwersytet Zielonogórski)
The heat sink dissipates heat from the hot source to the environment. Also, the heat sink can absorb heat from the hot surroundings. It comes in various designs. Electric and electronic equipment, chemical industries, refrigeration, air conditioning systems, power plants, and other thermal applications use this technology. A fin array, a metal device that uses passive and active cooling techniques to dissipate heat.
Keywords: heat sink design; longitudinal fin; performance of a heat sink; improving fin performance; fin optimization